Role of Prebiotics and Probiotics in Regulating Gut Health and Maintaining Healthy Normal Flora of Animals - Ishaq, Muhammad; Ibrahim, Jaweria; Shahbaz Ul Haq; Hayat, Muhammad Nasir; Ahmad, Mushtaq; Rauf, Umber; Adrian Shah, Shahzada Khurram; Zafar, Maham; Said Jamil; Shafiq Ur Rehman (Indus Journal of Bioscience Research, 2024)
Animals’ gastrointestinal (GI) tract harbors complex microbiota crucial for digestion, immunity, and overall health. Disruptions in this microbial ecosystem, such as dysbiosis, can lead to various health issues, including reduced immunity and poor nutritional absorption. This study explored the role of prebiotics and probiotics in modulating gut health and maintaining healthy microbial balance in animals. The effects of prebiotics, such as inulin and fructooligosaccharides (FOS), and probiotics, including Lactobacillus and Bifidobacterium, were investigated through experimental design. The findings from a randomized controlled trial on rats showed that prebiotics promoted the growth of beneficial bacteria, such as Lactobacillus and Bifidobacterium. At the same time, probiotics helped restore microbial equilibrium during dysbiosis. Both treatments were associated with improved gut microbiota diversity, enhanced immune responses, and reduced gastrointestinal complications. Notably, the combined application of prebiotics and probiotics exhibited a synergistic effect, emphasizing their potential as noninvasive and cost-effective solutions for promoting gut health. This study highlights the importance of prebiotics and probiotics as therapeutic interventions to maintain normal gut flora and improve animal well-being in veterinary and livestock management. These insights contribute to the ongoing search for sustainable and effective animal health and husbandry strategies, particularly in light of growing concerns about antibiotic resistance in agricultural systems. These results also underscore the need for further research on combining prebiotics and probiotics to optimize gut health across different animal species